Fidelity and robustness analysis of SVD-based image watermarking schemes - Del Colle, Franco A. (2011)
In this paper, an SVD-based perceptual fidelity metric is reviewed and used in the context of objective quantification of image watermarking fidelity for two stateof- the-art Image Adaptive SVD-based Watermarking Schemes. The proposed metric makes use of a Human Visual System perceptual model in the wavelet domain. The robustness of the watermarking schemes against JPEG compression and resizing is also tested on an image dataset of natural color images.